2008
DOI: 10.1080/10934520701792803
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity evaluation of five pharmaceutical pollutants detected in surface water on germination and growth of cultivated and spontaneous plants

Abstract: The phytotoxicity of 5 pharmaceuticals detected in Italian rivers, atorvastatin (7-[2-(4-fluorophenyl)-3-phenyl-4-(phenylcarbamoyl)-5-propan-2-yl-pyrrol-1-yl]-3,5-dihydroxy-heptanoic acid), gemfibrozil (5-(2,5-dimethylphenoxy)-2,2-dimethyl-pentanoic acid), tamoxifene (2-[4-(1,2-diphenylbut-1-enyl)phenoxy]-N,N-dimethyl-ethanamine), ethinyl estradiol (17-ethynyl-13-methyl-7,8,9,11, 12,13,14,15,16,17-decahydro-6H-cyclopenta[a]phenanthrene-3,17-diol) and sildenafil (methyl-9-propyl-2,4,7,8-tetrazabicyclo[4.3.0] no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…A soil contaminated with 3 ng g À1 of ibuprofen was used for remediation, taking into account the levels found in soil (Gibson et al, 2010;Aznar et al, 2014;Li, 2014). L. sativa (lettuce) was chosen to evaluate the phytotoxic effects of an ibuprofen contaminated soil before and after the application of the two above-mentioned soil remediation treatments, since this is a standard species recommended for phytotoxic studies (OECD, 2006;D'Abrosca et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A soil contaminated with 3 ng g À1 of ibuprofen was used for remediation, taking into account the levels found in soil (Gibson et al, 2010;Aznar et al, 2014;Li, 2014). L. sativa (lettuce) was chosen to evaluate the phytotoxic effects of an ibuprofen contaminated soil before and after the application of the two above-mentioned soil remediation treatments, since this is a standard species recommended for phytotoxic studies (OECD, 2006;D'Abrosca et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CBZ and ibuprofen do not have toxic effects on ryegrass (Winker et al, 2010), and CBZ, diphenhydramine, and triclocarban do not have toxic effects on various crops (Wu et al, 2012). However, other studies have indicated that the uptake of drugs can inhibit plant growth and induce damage to plants (Boxall et al, 2006;Michelini et al, 2012;Dolliver et al, 2007;Shenker et al, 2011;D'Abrosca et al, 2008, Aristilde et al, 2010Eggen et al, 2011).…”
Section: Effects Of Pac On In Vitro Germination and Plant Growthmentioning
confidence: 99%
“…Although L. sativa cannot be considered a representative species of the aquatic environment, the results generated in this assay can be used to evaluate the possible toxic effects of contaminants on plants that live near polluted water bodies (Sobrero and Ronco, 2004) or as a result of irrigation with reused water if contaminants are not fully removed in predicting treatment. Furthermore, it is a representative of main dicotyledon commercial crops and considered a standard species due to moderate sensitivity and high frequency of use in phytotoxicological tests (D'Abrosca et al, 2008;Hillis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%